Performance study of UEI based on the relatively matching of energy supply-demand information entropy. (October 2018) - Gong, Z P; Qiu, L; Tang, L H; Zhu, X J; Gan, Z X
Abstract: This paper studies the performance of UEI (Ubiquitous Energy Internet) by means of its energy supply-demand matching degree. First of all, the energy supply-demand matching degree of UEI is defined, and then the information entropy of energy supply-demand match degree is defined either by use of Shannon's information entropy theory. On the basis of these two definitions, the energy matching degree information entropy of the distributed Energy Internet is defined. By the study of information entropy characteristic and energy supply-demand matching degree, the evaluation model of energy supply-demand matching degree of UEI is provided, and the performance of UEI is evaluated. Finally, the effectiveness of this evaluation model in solving the supply-demand performance evaluation problem of UEI is proved by an example.